2020
DOI: 10.3389/fpsyg.2020.02069
|View full text |Cite
|
Sign up to set email alerts
|

Just What I See? Implications of Congruence Between Supervisors’ and Employees’ Perceptions of Pay Justice for Employees’ Work-Related Attitudes and Behaviors

Abstract: Perceiving a pay system as just has been suggested to be a precondition for individualized pay to have a motivating effect for employees. Supervisors' enacted justice is central for understanding the effects that pay setting can have on employee attitudes and behavior. Yet, enacted justice has received little research attention, in regard to both organizational justice and pay-related topics. This study examines the effects of employees' perceived pay justice and supervisors' enacted justice, as well as the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 80 publications
(182 reference statements)
2
9
0
1
Order By: Relevance
“…However, the main contribution of the present study is that it shows the importance of employee preparations, the usage of explicit criteria in performance appraisal/wage determination, the quality of the performance appraisal dialogue and feedback, and the evaluation style of the manager in the appraisal. To some extent, our findings are in line with theoretical reasoning and empirical indications scattered in various previous research (Choi & Whitford, 2017; Favero et al, 2016; Gerhart & Fang, 2015; Glassman et al, 2010; Lee, 2019; Malmrud et al, 2020; Oh & Lewis, 2009; Schay & Fisher, 2013). However, these variables have seldom been at the center of the analysis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, the main contribution of the present study is that it shows the importance of employee preparations, the usage of explicit criteria in performance appraisal/wage determination, the quality of the performance appraisal dialogue and feedback, and the evaluation style of the manager in the appraisal. To some extent, our findings are in line with theoretical reasoning and empirical indications scattered in various previous research (Choi & Whitford, 2017; Favero et al, 2016; Gerhart & Fang, 2015; Glassman et al, 2010; Lee, 2019; Malmrud et al, 2020; Oh & Lewis, 2009; Schay & Fisher, 2013). However, these variables have seldom been at the center of the analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Theoretically, the results confirm aspects of both justice-perceptions (Colquitt, 2001;Malmrud et al, 2020), and SDT (Gerhart & Fang, 2015;Ryan & Deci, 2000). Employee motivation increased with information and fair feedback, and through a good dialogue regarding performances and future possibilities.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Brebels et al, 2011;Hoogervorst et al, 2013;Zapata et al, 2013). In general, research has found substantial correlations between supervisors' self-reported justice enactment and employees' justice perceptions (Huang et al, 2017;Zapata et al, 2013), although some studies have also found manager reports of enacted justice to be unrelated to their subordinates' perceptions of justice (Malmrud et al, 2020).…”
Section: Antecedents Of Self-reported Justice Enactmentmentioning
confidence: 99%